IMPLEMENTASI 5R UNTUK MENCEGAH PENYAKIT AKIBAT KERJA PADA GIGI DAN MULUT SERTA SALURAN PERNAFASAN DI INDUSTRI INFORMAL SRAGEN - Haris Setyawan; Ipop Sjarifah (Jurnal Kesehatan Gigi, 2015)
TITLEIMPLEMENTATION OF 5R TO PREVENT OCCUPATIONAL DISEASES IN SRAGEN INFORMAL INDUSTRY TO DENTAL, ORAL AND RESPIRATORY TRACT HEALTHABSTRACTPilang village in Sragen are famous for the production of batik clothes that still using manual processes to produces the batik. Most of the batik industry in this village produced for local industry that is not familiar with the implementation of health and safety, that caused many complaining of occupational diseases in workplace. The one of occupational disease is a disease of the teeth and the mouth and respiratory  that indicated caused from dye clothing, wax and smoke from burning wood and gas for drying the batik fabrics motif by workers. To prevent the impact of occupational illness, one preventive method that can be used is the 5R.Respondents are batik workers at the Pilang village in Masaran District of Sragen that total respondents are 37 peoples. The method that used in hazard identification, risk assessment and determinating control (HIRADC). After the a priority scale through the model of HIRADC determinated, then performed the corrective actions taken by using a hierarchy of control especially the 5R methods.The workers of Batik Industry in PilangVillage has exposure the CO gas that exceeds the threshold value at 69-90 ppm, and temperature humidity index at 32.5-33.50C. Especialy for behavioral factors is working without personal protective equipment that are harmful to health due to exposure to gas and dye clothing. Key words : 5R, batik workers, occupational diseases, dental mouth disease, respiratory problems